Things that move a hinterland in architectural history - Anstey, Tim 1965- (The MIT Press, 2024)
"Things that Move presents eight interconnected essays that collectively explode the myth of architecture as the realm only of the static, and instead advocates movement as the single dynamic for understanding architecture's recent and distant past"--
Keywords: Fontana, Domenico -- 1543-1607; Warburg Institute -- Library; Geschichte 1530-1910; Geschichte 1450-1590; Geschichte; Decorum; Architekturtheorie; Architektur; Schiffbau; Transport; Verkehrsbau; Bewegung; Obelisco Vaticano -- Rom; Slussen Stockholm; Architecture / History; Movement (Philosophy); Architecture / Histoire; Mouvement (Philosophie); Architecture; History